Risk-Taking Behaviors in Children with ADHD Compared to Children with Primary Headaches - Winter, Gidon Nathan; Aran, Adi; Pollak, Yehuda (Neuropediatrics, 2023)
The study examined the engagement in risk-taking behaviors and their onset in children with attention-deficit/hyperactivity disorder (ADHD) compared with children with primary headaches. Whether ADHD is associated with higher engagement in risk-taking behavior compared with other neurodevelopmental disorders (and not only typical development) has yet to be demonstrated. A sample of 189 children, 10 to 18 years old, undergoing neurological surveillance for ADHD (N = 144) or primary headaches (N = 45) participated in the study. The children and their parents reported the children's engagement in various risk-taking behaviors. The ADHD group reported a higher level of general risk-taking behavior relative to the headache group. The differences remained significant even after controlling for demographic and clinical variables. No differences in the age of onset of risk-taking behaviors were found. It is concluded that risk-taking behavior is more common in children with ADHD under active neurological surveillance than in children followed for primary headaches.
Keywords: ADHD; primary headaches; risk-taking behavior